Discordant Prenatal Cell-Free DNA Screening vs. Diagnostic Results of Sex Chromosome Aneuploidies: Implications for Newborn Screening and Genetic Counseling - Susan Howell; Shanlee M. Davis; Billie Carstens; Mary Haag; Judith L. Ross; Nicole R. Tartaglia (MDPI AG, 2024)
Sex chromosome aneuploidies (SCAs) collectively occur in 1 in 500 livebirths, and diagnoses in the neonatal period are increasing with advancements in prenatal and early genetic testing. Inevitably, SCA will be identified on either routine prenatal or newborn screening in the near future. Tetrasomy SCAs are rare, manifesting more significant phenotypes compared to trisomies. Prenatal cell-free DNA (cfDNA) screening has been demonstrated to have relatively poor positive predictive values (PPV) in SCAs, directing genetic counseling discussions towards false-positive likelihood rather than thoroughly addressing all possible outcomes and phenotypes, respectively. The eXtraordinarY Babies study is a natural history study of children prenatally identified with SCAs, and it developed a longitudinal data resource and common data elements with the Newborn Screening Translational Research Network (NBSTRN). A review of cfDNA and diagnostic reports from participants identified a higher than anticipated rate of discordance. The aims of this project are to (1) compare our findings to outcomes from a regional clinical cytogenetic laboratory and (2) describe discordant outcomes from both samples. Twenty-one (10%), and seven (8.3%) cases were found to be discordant between cfDNA (result or indication reported to lab) and diagnosis for the Babies Study and regional laboratory, respectively. Discordant results represented six distinct discordance categories when comparing cfDNA to diagnostic results, with the largest groups being Trisomy cfDNA vs. Tetrasomy diagnosis (66.7% of discordance in eXtraordinarY Babies study) and Mosaicism (57.1% in regional laboratory). Traditional genetic counseling for SCA-related cfDNA results is inadequate given a high degree of discordance that jeopardizes the accuracy of the information discussed and informed decision making following prenatal genetic counseling.